First thoughts - Griffith, Peter; Millbank Films (Hong Kong : Educational Film Services, 1984)
Follows a retail clerk, a machinist and an electrical worker on their first day of work, showing the safety training they receive and the precautions theypractice
Keywords: Safety education, Industrial